المجتمع المدني ضرورة وظيفية للدولة - الحوراني, محمد عبد الكريم (Sciences de l'Homme et de la Société; Vol. 8 (2013): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
لقد أظهرت الدراسة أن المجتمع المدني يعمل على بناء المسؤولية الجمعية، والتشاركية وتحسين الأداء الحكومي. كما يضع الظروف المواتية للديمقراطية، ويجسد البنية التي تضمن حق الناس في الاعتراض والاحتجاج ويقوي الممارسات الديمقراطية، ويولد الولاء الحقيقي والمواطنة، كما أظهرت الدراسة أن شرعية الدولة مرتبطة بحضور المجتمع المدني كتعبير عن الإرادة الحرة للمواطنين، كما أن المجتمع المدني يبني شرعية الدولة على أساس المسؤولية الأخلاقية، ويجنب الدولة مأزق أزمة الشرعية.   The study showed that civil society structuring the collective responsibility, participatory, and improving the governmental performance, Besides, civil society puts an appropriate conditions for democracy, and embodies the structure that ensures the peoples right to object and protest, strengthening democratic practices and generates the genuine loyalty and citizenship. In addition, the study showed that legitimacy of state is connected to the presence of civil society which expresses the free will of citizens, Also, civil society Structuring the legitimacy of state in the base of moral responsibility, and avoiding state the dilemma of legitimacy crisis.